A Contemporary Interpretation of Tradition in Mosque Design. Marmara Ilahiyat Mosque, Turkey - Erarslan, Alev (European Scientific Journal, ESJ, 2019)
In recent years, the concept of contemporary mosque architecture has emerged in all Islamic countries. The goal of these structures which are produced using original designs, contemporary materials, technology and construction systems is to design structures which suit modern architectural concepts of today in the architecture of traditional mosques. Taken up with contemporary plan and form concepts rather than traditional plans, contemporary lines and interpretations are seen in liturgical elements such as the mihrap, dais, pulpit, gallerys, courtyard, fountain and minaret, which are indispensable elements of the mosque architecture in these mosques. One of the important points that is dwelled upon with these structures is their interior design. The aim of this study is to examine the design, layout features as well as the interior decoration of the Marmara Ilahiyat Mosque, which is one of our contemporarymosques that have been addressed in Turkey in the 20th century. With this goal, the structure’s overall layout, its interior space, decorative and liturgic elements as well as characteristics such as materials, technology and lighting have been examined in detail. As one of the important representatives of contemporary Turkish mosques, the structure is suitable for the land it was built on top of and the city fabric, that it interprets traditional architecture with modern styling, and that it takes its place in a significant position amongst contemporary Turkish mosques, as it is a unique example that achieves a contemporary and dynamic identity of Turkish-Islamic architectures by using today’s materials and techniques from a standpoint of traditional layout, plan elements and interior space embellishments.